2024
DOI: 10.1111/raq.12900
|View full text |Cite
|
Sign up to set email alerts
|

Salinity tolerance of fishes: Experimental approaches and implications for aquaculture production

Andre P. Seale,
Ke Cao,
Ryan J. A. Chang
et al.

Abstract: The life history, distribution and diversity of fishes are largely influenced by environmental salinity. Changes in salinity affect a range of physiological processes including metabolism, nutrition, reproduction and growth. Therefore, fish can be conditioned to environmental parameters most suitable for production, where distinct traits are optimised through species‐specific manipulation of salinities. The primary purpose of this review is to summarise the existing literature on the salinity tolerance of aqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 268 publications
0
1
0
Order By: Relevance
“…Myers based his classification on frequent observations of secondary species in coastal habitats or in hyperhaline waters, or the fact that they had been able to cross the sea and reach islands such as Madagascar, the Seychelles, or the West Indies, in contrast to primary species (Myers, 1949). Recent reviews of existing experimental studies have demonstrated that in general, primary species such as cyprinids, characids and most siluriforms demonstrate lower salinity tolerance compared with secondary and peripheral species Seale et al, 2024). In fact, some secondary fish species from diverse phylogenetic origins (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Myers based his classification on frequent observations of secondary species in coastal habitats or in hyperhaline waters, or the fact that they had been able to cross the sea and reach islands such as Madagascar, the Seychelles, or the West Indies, in contrast to primary species (Myers, 1949). Recent reviews of existing experimental studies have demonstrated that in general, primary species such as cyprinids, characids and most siluriforms demonstrate lower salinity tolerance compared with secondary and peripheral species Seale et al, 2024). In fact, some secondary fish species from diverse phylogenetic origins (e.g.…”
Section: Introductionmentioning
confidence: 99%